Antibacterial and cytotoxic properties of endophytic extracts for oral application - Doll-Nikutta Katharina; Caruso Daniel; Firoozbahr Meysam; Winkel Andreas; Zaferanloo Bita; Stiesch Meike (Current Directions in Biomedical Engineering)
Endophytic fungal extracts possess great potential as alternative antibacterial substances. Here, two extracts from the Australian endemic plant Eremophila longifolia were shown to reduce biomass and metabolic activity of the oral bacteria Streptococcus oralis and Porphyromonas gingivalis. As the effective concentration towards S. oralis was lower than the cytotoxic concentration towards oral epithelial cells, more detailed studies are warranted in the future.